Determinants of Typical Errors in Interpretation of ECHR Provisions in the Jurisprudence of Ukraine. - Карвацька, Світлана Богданівна (My University, 2021)
The article will examine the determinants of typical errors in the interpretation of ECHR provisions in the jurisprudence of Ukraine. It will prove that the ratification of the ECHR by Ukraine has begun the process of changing the dominant positivist paradigm of law, which has led to the emergence of legal theory and the implementation of the necessary for the further development of pluralism. At the same time, such a process immediately provoked lively discussions around the problem of interpreting the content of the requirements laid down in the Convention. Nevertheless, the problem is that there is no consensus among researchers on understanding the general question of the place of ECHR decisions in the Council of Europe member state’s internal legal system. It can be stated that in the analyzed cases, the Ukrainian courts have interpreted the same ECtHR decision differently, resulting in a violation of one of the conceptual principles - the unity of interpretation and unambiguous application of ECtHR practice. It will be substantiated that a totality of these points leads to a logical conclusion. Despite the legislative consolidation of the status of ECtHR decisions as a source of law in Ukraine, the factors hampering the proper application of ECtHR practices are the lack of a systematic and valid methodology for formulating and motivating court decisions using an effective interpretative interpretation ECtHR regarding specific decisions.
Keywords: interpretation of international law, Vienna Convention on International Treaties of 1969, ECHR, national legal system of Ukraine.